EMPOWERED CUSTOMERS IN THE GROCERY SECTOR: AN ANALYSIS OF COMMENTS POSTED BY CUSTOMERS ON FACEBOOK - Peeroo, Swaleha (PEOPLE: International Journal of Social Sciences, 2017)
Businesses across a wide array of industries have rushed to adopt social media as a marketing strategy.Social media have transformed the communication landscape since customers now have the possibility to create content on social media sites of businesses and share their lived experiences with the online community. Increasingly, grocery stores are using Facebook to communicate with customers. However, there is paucity of research on the use of social media in the grocery sector. This paper aims to determine whether and investigate how Facebook has empowered customers of Tesco and Walmart. Netnography approach was adopted to observe the social media phenomenon within the grocery sector. Contents posted on the Facebook page of Tesco and Walmart were collected to explore how Facebook has empowered grocery customers. Findings show that Facebook has given a voice to the customer. Customers of Tesco and Walmart have the power to gain information, the power to complain and to criticise, the power to create value and the power to provide information to the community. This paper contributes to knowledge by revealing how Facebook has empowered grocery customers. Future research could focus on customer empowerment in anti brand communities or other online sources where customers exchange information on brands.